Evaluation of the efficiency of chemical cartridges for respiratory protection against SARS-CoV-2. Issue 1 (31st December 2022) - Paiva, José D.; Neto, Paulo C.
Abstract: The shortage of PFF2, N95, KN95, and FFP2 respirators in the COVID-19 pandemic required that alternative respiratory protection measures be adopted to reduce the number of cases of the disease. Given this scenario, with the purpose of proving that chemical cartridges offer some degree of protection against aerodispersoids, among these those of biological origin, such as SARS-CoV-2, the filtering efficiency of chemical cartridges was evaluated. The evaluation of the filtering efficiency of cartridges was performed using the air filter test method, which uses micrometric air particles for the penetration test. The research proved that chemical cartridges, in general, have an average efficiency above 85% for respiratory protection against aerodispersoids. The multigas cartridge and organic vapor/acid gas cartridge had an average filtration efficiency of 91%. Chemical cartridges associated with facial or semi-facial respirators can become powerful resources for respiratory protection for people exposed to the virus, when the use of PFF2 or equivalent respirators is not possible.